Contrasting recruitment seasonality of sea urchin species in Gran Canaria, Canary Islands (eastern Atlantic) - GARCIA-SANZ, S.; NAVARRO, P. G.; TUYA, F. (Mediterranean Marine Science, 2014)
Despite sea-urchins can play an important role affecting the community structure of subtidal bottoms, factors controlling the dynamics of sea-urchin populations are still poorly understood. We assessed the seasonal variation in recruitment of three sea-urchin species (Diadema africanum, Paracentrotus lividus and Arbacia lixula) at Gran Canaria Island (eastern Atlantic) via monthly deployment of artificial collectors throughout an entire annual cycle on each of four adjacent habitat patches (seagrasses, sandy patches, ‘urchin-grazed’ barrens and macroalgal-dominated beds) within a shallow coastal landscape. Paracentrotus lividus and A. lixula had exclusively one main recruitment peak in late winter-spring. Diadema africanum recruitment was also seasonal, but recruits appeared in late summer-autumn, particularly on ‘urchin-grazed’ barrens with large abundances of adult conspecifics. In conclusion, this study has demonstrated non-overlapping seasonal recruitment patterns of the less abundant species (P. lividus and A. lixula) with the most conspicuous species (D. africanum) in the study area.